Migration in West Africa IMISCOE Regional Reader - Teye, Joseph Kofi (IMISCOE Research Series, 2022)
This open access Regional Reader examines the dynamics and impacts of international migration within and from West Africa. The book presents key theoretical perspectives and empirical findings on historical trends, geographical patterns, drivers and socio-economic impacts of both voluntary and involuntary migration in West Africa, a region that is characterised by high level of mixed migration flows. The book is divided into three main parts: changing patterns and governance of migration, managing environmental and forced migration, and diaspora, transnationalism and development. The chapters raise key research questions and outline recommendations for improving migration governance, protecting migrants and harnessing the benefits of migration for socio-economic development for both countries of origin and destination of migrants. As such this Regional Reader provides an interesting read to students, academics, researchers, migration experts, development practitioners and policy makers.